SISTEM ADMINISTRASI LAB KOMPUTER BERBASIS WEB DI SMK NURUL ULUM MANGAR - Irwan Darmawan; Mohammad Nazir Arifin; Anang F Rachman; Mohammad Ma’ruf (Universitas Pahlawan Tuanku Tambusai, 2022)
The computer laboratory department of SMK Nurul Ulum currently still has not implemented the concept of information systems in its laboratory management. The procedures for daily activities are still carried out manually so that the use of computers is only limited to making practicum schedules, and typing reports. Furthermore, there is no specific program or application that can be used to process these data. In addition, neither damage nor damage handling has ever been recorded properly. The amount of damaged or lost inventory cannot be controlled because it is not recorded neatly. Based on the problems that exist in the computer laboratory of SMK Nurul Ulum, researchers are interested in making a lab management administration application for computer laboratory management that can help in processing data so that it can produce easier and more accurate information. Keywords: laboratory, SMK Nurul Ulum